2020
DOI: 10.3390/medicina56120671
|View full text |Cite
|
Sign up to set email alerts
|

On the Quest for In Vitro Platelet Production by Re-Tailoring the Concepts of Megakaryocyte Differentiation

Abstract: The demand of platelet transfusions is steadily growing worldwide, inter-donor variation, donor dependency, or storability/viability being the main contributing factors to the current global, donor-dependent platelet concentrate shortage concern. In vitro platelet production has been proposed as a plausible alternative to cover, at least partially, the increasing demand. However, in practice, such a logical production strategy does not lack complexity, and hence, efforts are focused internationally on developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 132 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…Moreover, since abnormal morphological changes in platelets are associated with pathophysiological conditions, the regulation of platelet cytoskeletal dynamics must be explored in the process of drug discovery for novel PAR4 antagonists [ 47 ]. However, platelets used for research purposes are currently donor-derived, which is associated with some important limitations in terms of short shelf life, donor dependency, and donor variability [ 24 , 48 ]. Here, we showed that MEG-01 cells functionally express PAR1 and PAR4, and that thrombin induce morphological changes in MEG-01 cells through PAR1 and PAR4 activation, such as that observed in human platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since abnormal morphological changes in platelets are associated with pathophysiological conditions, the regulation of platelet cytoskeletal dynamics must be explored in the process of drug discovery for novel PAR4 antagonists [ 47 ]. However, platelets used for research purposes are currently donor-derived, which is associated with some important limitations in terms of short shelf life, donor dependency, and donor variability [ 24 , 48 ]. Here, we showed that MEG-01 cells functionally express PAR1 and PAR4, and that thrombin induce morphological changes in MEG-01 cells through PAR1 and PAR4 activation, such as that observed in human platelets.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ideas of platelet generation in vitro have been proposed, and many laboratories have successfully differentiated megakaryocytes into platelets in vitro. However, the large-scale production of platelets is still a challenging task in vitro [ 17 ].…”
Section: Introductionmentioning
confidence: 99%